2019
DOI: 10.24059/olj.v1i2.1934
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of college-level courses via Asynchronous Learning Networks: Some Preliminary Results

Abstract: New Jersey Institute of Technology has been delivering college courses via an Asynchronous Learning Network (ALN) system called the Virtual ClassroomTM for a decade, using various media mixes. Currently, two complete undergraduate degree programs are available via a mix of video plus Virtual Classroom, the B.A. in Information Systems and the B.S. in Computer Science. This paper presents preliminary findings about impacts on students, and touches on some issues and potential impacts for faculty, individual univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 6 publications
1
39
0
2
Order By: Relevance
“…When online programs compete with face-to-face instruction to produce equivalent learning, dropout rates become a concern for technology-mediated learning. Studies showed that dropout rates in distance learning were higher than those in traditional learning, and that dropout rates indicated academic non-success (Diaz, 2000;Hiltz, 1997;Phipps & Merisotis, 1999;Rofle, 2007). Though "the mere fact of high drop rates is not necessarily indicative of academic non-success" (Diaz, 2002, para. 3), dropout issues still had to be addressed in order to advance online teaching and learning (Alexander, 2002;Park, 2007).…”
Section: Attrition In Distance Learningmentioning
confidence: 99%
“…When online programs compete with face-to-face instruction to produce equivalent learning, dropout rates become a concern for technology-mediated learning. Studies showed that dropout rates in distance learning were higher than those in traditional learning, and that dropout rates indicated academic non-success (Diaz, 2000;Hiltz, 1997;Phipps & Merisotis, 1999;Rofle, 2007). Though "the mere fact of high drop rates is not necessarily indicative of academic non-success" (Diaz, 2002, para. 3), dropout issues still had to be addressed in order to advance online teaching and learning (Alexander, 2002;Park, 2007).…”
Section: Attrition In Distance Learningmentioning
confidence: 99%
“…Despite their affordances, the actual benefits of AODs in large groups (i.e., 30 students or more as defined in Hiltz [10]) are not clear. One reason considers disorientation.…”
Section: Introductionmentioning
confidence: 99%
“…Hiltz (1997) provides an overview of asynchronous learning environments that would seem to be the best of all possible educational worlds: The fact that the educational process is asynchronous means students may engage in more reflective thinking before having to answer or discuss issues, as compared to a synchronous or same-time interaction, and it also means that students can participate at their own convenience, and thus better fit the demands of a college degree program into busy lives. Working in such an environment requires a series of best practices providing '"the means to create the feeling of a true 'class' or group of people who are learning together, and by structuring and supporting a carefully planned series of collaborative learning activities which constitute the assignments for the course" (Hiltz, 1997). Hiltz shares with Johnson and Johnson (1975), and Dillenberg and Schneider (1995), the belief that collaborative learning is "a learning process that emphasizes group or cooperative efforts among faculty and students.…”
Section: Distrexjted L E a R " G E " M E N T Smentioning
confidence: 99%
“…Individuals or small groups of students are responsible for making a selection of a topic; reading material not assigned to the rest of the class; preparing a written summary for the class of the most important ideas in the material; and leading a discussion on the topic or material for which they are responsible." (Hiltz, 1997) This practice has it cognates in PBL activities and constructivist philosophies.…”
Section: Distrexjted L E a R " G E " M E N T Smentioning
confidence: 99%